FACTORS THAT INFLUENCE PROSOCIAL BEHAVIOR IN VOLUNTEERS OF RUMAH ZAKAT YOGYAKARTA - Rina Istiqomawati; Andriyani Widiyastuti; Hanan Wihasto (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
One of the organizations involved in social activities is Rumah Zakat. Rumah Zakat as an organization requires human resources in its management, these human resources are Rumah Zakat volunteers. Volunteers are the key to the success of a Rumah Zakat institution, therefore the need for volunteers is very important for the fulfillment of Rumah Zakat's goals. People who help selflessly and provide benefits to others rather than themselves include prosocial behavior. In prosocial behavior there are several factors that influence it, namely situational factors, helpers and people who need help. The purpose of this study is to find out how prosocial behavior in Yogyakarta zakat house volunteers, to find out what factors influence prosocial behavior in Yogyakarta zakat house volunteers and what dominant factors influence prosocial behavior in Yogyakarta zakat house volunteers. This research uses a quantitative paradigm with descriptive research design. The samples to be used in this study amounted to 25 of the Yogyakarta zakat house volunteers who are currently still actively carrying out volunteer activities. The data collection technique used is the questionnaire technique. The data analysis technique uses descriptive analysis techniques and factor analysis. The results of research on data analysis and discussion of the factors that influence prosocial behavior in Yogyakarta zakat house volunteers can be concluded that the prosocial behavior of zakat house volunteers is included in the moderate category. factors that influence prosocial behavior in zakat house volunteers consist of the presence of others, environmental conditions, time pressure, personality factors, mood, guilt, distress and empathy, helping people who are liked helping people who deserve help. The more dominant factors influencing prosocial behavior in zakat house volunteers are distress and empathy.